Optimization of reliability and maintenance of liquefaction system on FLNG terminals using Markov modelling. Issue 3 (25th February 2014) - Gowid, Samer; Dixon, Roger; Ghani, Saud
Abstract : Purpose: – The purpose of this paper is to optimize system redundancy and maintenance intervals of a propane pre-cooled mixed refrigerant (C3MR) liquefaction process on floating liquefied natural gas (FLNG) export platforms. Design/methodology/approach: – The reliability modeling is based on the time-dependent Markov approach. Four different system options are studied, with various degree of redundancy. Failures in the liquefaction system usually lead to shutdown the whole LNG production plant. The associated shutdown cost is compared with the cost of introducing redundancy and the cost of onboard maintenance. To ensure a high profitability, a model for maintenance optimization is utilized and applied to the main unit of the C3MR liquefaction system to minimize the onboard maintenance cost. Findings: – The results indicated that the introduction of a second liquefaction system (as a standby unit) is the best option for liquefaction plant in terms of reliability and cost. This will substantially reduce the unavailability from 14.7 to 2.19 percent of the total operational hours. Based on the presented system configuration, the annual system profit will increase by 180 million USD if the redundancy is implemented on FLNG export ships. The optimum maintenance intervals of major process components are also calculated to minimize the total cost of maintenance. Originality/value: – The originality of this paper lies within the context in investigating the reliability of the C3MR liquefaction system on LNG floating export terminals using Markov modeling for the first time.